Anthropologist and Administrator - Buswell, James Oliver (Practical anthropology, 1961)
By “administrator” the author refers to any individual who is involved in directing or stimulating culture change, whether he be missionary, educator, industrialist, or government official. The principal data of this article are taken from government administration of colonial areas because it is in this field that there has been the greatest degree of anthropological discussion. Much of the theory behind these phases of applied anthropology has been summarized in the previous article in this series, “From Anthropology in Action to Action Anthropology.”1 In the present article the author describes the problems, the conflicts, the degrees of cooperation, and the practical usefulness of the collaboration of anthropologist and administrator.